Disparitas Pemidanaan dalam Tindak Pidana Penambangan Tanpa Izin: Analisis Putusan Nomor 44/Pid.B/2021/PN Amp Ditinjau dari Tujuan Pemidanaan dan Efektivitas Penegakan Hukum - Farida Nurun Nazah; Delvi Eka Ariyanti; Elika Maulidia; Talitha Kamilah; Michel Priscila; Ismaya Rahailia Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Illegal mining operations (PETI) cause permanent ecological destruction and substantial state financial losses. Using a comprehensive normative legal approach, this article carefully examines the lenient sentence in Judgment Number 44/Pid.B/2021/PN Amp regarding enforcement efficiency and returning heavy machinery to owners. The study reveals a sharp sentencing disparity; the offender received only two months' imprisonment. The judges' rigid legalistic-formal adherence completely overlooked tangible environmental damage. Returning the leased excavator weakens deterrence and inherently legitimizes illegal exploitation. Thus, environmental law supremacy remains suboptimal. Judges must adopt progressive legal steps through the polluter pays doctrine to ensure future ecological justice for the public